Physical Self-Schema Acceptance and Perceived Severity of Online Aggressiveness in Cyberbullying Incidents - Roman, Alina; Rad, Dana; Egerau, Anca; Dixon, Daniel; Dughi, Tiberiu; Kelemen, Gabriela; Balas, Evelina; Rad, Gavril (Journal of Interdisciplinary Studies in Education, 2020)
In this study, physical self-schema referred to the perceived body image youths have over their physical appearance. There is a pool of research that links the perceived physical self-schema to perceived severity of online aggressiveness. This research suggests that the better the physical self-schema perception is, the least youth consider the severity of online aggressiveness towards peers. The project KYSFC was developed to provide an in-depth understanding of the interactions between different psychological aspects of cyberbullying in adolescents. Using a two item online questionnaire, the study analyzed the effect of physical self-schema acceptance on perceived severity of online aggressiveness in cyberbullying. Five hundred and seven students from Belgium, Spain, Romania, and Turkey participated in the survey. When mapping effects of physical self-schema acceptance on perceived negative effect of online aggressiveness, the curvilinear interaction model (2%) is more robust that the linear interaction model (0.8%), when both models are statistically significant.